Fenomena Praktik Ijtihad dan Taqlid dalam Pandangan Hukum Islam - Syarif Muhammad Yahya (Prodi Hukum Ekonomi Syariah (Muamalah), 2021)
This paper aims to analyze the extent of ijtihad and taqlid perspectives according to classical andcontemporary scholars. Understanding the scope of mujtahid and muqallid requirements and urgencyin Islamic Fiqh. The writing method used is a literature review method which is included in the categoryof textual historical research regarding the content of ijtihad. Sources of research through primary,secondary, and tertiary data obtained from literature, documentation, and expert opinion. The resultscan be concluded that the prospect of ijtihad in the current era is actually still wide open for thosewho have full competence, unfortunately it is still quite difficult to realize due to several obstaclesincluding one, many scholars think that after the third period the door of ijtihad has been closed, andalthough it is possible, it is possible Ijtihad is only at the level of muqayyad and not mustaqil. Two, thedifference in perspective on the boundaries of the legal object of ijtihad often creates conflicts andmakes intellectuals afraid and empty. Three, the actualization of Islamic law is still only a discoursewithout any continuity